Genome-wide identification and expression analysis of MIKCC genes in rose provide insight into their effects on flower development - Wang, Yi; Yang, Tuo; Li, Yuqi; Hou, Jialin; He, Junna; Ma, Nan; Zhou, Xiaofeng (Frontiers in Plant Science, 2022)
The MIKCC-type gene family plays important roles in plant growth, development, and tolerance of biotic and abiotic stress, especially during floral organ differentiation. However, there have been no studies of MIKCC-type genes in rose, and functional differentiation of family members has not been explored. In this study, we identified 42 MIKCC-type genes in rose, classified the genes into 12 subfamilies, and constructed a phylogenetic tree. We performed expression analysis of these genes, and found that expression patterns correlated with the predicted subfamily, indicating that the features of MIKCC-type genes were broadly conserved during evolution. Collinear analysis of MIKCC genes among Rosaceae species confirmed the occurrence of whole genome duplications (WGD) and revealed some species-specific MIKCC genes. Transcriptome analysis showed that the expression of some MIKCC-type genes responded to low temperatures (4°C, 24 h) during flower organ differentiation. These conserved, duplicated, and novel expression patterns of MIKCC-type genes may have facilitated the adaptation of rose to various internal and external environmental changes. The results of this study provide a theoretical basis for future functional analysis of the MIKCC genes in rose and investigation of the evolutionary pattern of the MIKCC gene family in the Rosaceae genome.